Security Environment and Strategic Stability in South Asia. - Masood, Talat (2005)
Security environment in South Asia has improved significantly considering that three years ago India and Pakistan were locked in a military standoff. Several military and civilian Confidence Building Measures (CBM’s) have been agreed, improving prospects of greater economic, cultural and political interaction. But progress of hard issue of Jammu and Kashmir, Siachen, Sir Creek and diversion of water resources remains disappointing. It is to be seen if the third round of talks could yield results. India has shown willingness to engage with the All Parties Hurreit Conference—the main Kashmiri opposition group, and also allowed their leadership to interact with Pakistan. Both countries are looking at cooperation in the field of energy, although opposition by U.S. to the Iranian gas pipeline could derail the project. India and Pakistan continue to build their nuclear arsenals and delivery systems. Recent “Global Partnership Agreement” between the United States and India and introduction of Ballistic Missile Defence (BMD) could have wide-ranging implications for regional stability, affecting Pakistan and also China. The challenge is to reconcile the military aspirations of India and Pakistans with the peace process so that they could focus on fighting poverty and improving the quality of life of their people. This would demand bold initiatives to resolve substansive issues and gradually move toward a strategic restraint regime.